2019
DOI: 10.4103/jispcd.jispcd_26_19
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of resin infiltrate in noncavitated proximal carious lesions: A systematic review and meta-analysis

Abstract: Objectives: Resin infiltration is a minimally invasive technique for treating noncavitated proximal caries. It slows/stops the carious lesion progression rate by creating a diffusion barrier inside the porous enamel lesion body. The aim was to evaluate the efficacy of resin infiltration on noncavitated proximal carious lesions in primary and permanent teeth. Materials and Methods: The records were obtained using electronic and other sources. The Preferred Reporting Item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
2
13
0
4
Order By: Relevance
“…The other reason was that most of the included studies were calculated with per-protocol analysis; however, some studies have argued that, in the split-mouth design, it is doubtful whether attrition will affect the overall risk of bias [ 13 , 27 ]. Thus to qualify the studies, when the drop-out rate was more than 25%, the missing data were regarded to have potential impacts on the results [ 13 , 31 ]. Finally, the lack of pre-registration of the this study would be of great risk since the same type of meta-analysis would be published repeatedly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other reason was that most of the included studies were calculated with per-protocol analysis; however, some studies have argued that, in the split-mouth design, it is doubtful whether attrition will affect the overall risk of bias [ 13 , 27 ]. Thus to qualify the studies, when the drop-out rate was more than 25%, the missing data were regarded to have potential impacts on the results [ 13 , 31 ]. Finally, the lack of pre-registration of the this study would be of great risk since the same type of meta-analysis would be published repeatedly.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers must answer signalling questions as follows: bias arising from the randomisation process, bias due to deviations from intended interventions, bias due to missing outcome data, bias measurement of the outcome, bias in selection of the reported result. In addition, drop-out rates less than 25% were regarded to have no substantial impacts of the failure based on previous studies [ 13 , 31 ]. Overall risk of bias judgement is shown: trials with at least 1 item regarded as high risk were identified as having a high risk of bias.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of attrition bias, some studies have argued that in the split-mouth design, it is doubtful whether attrition would affect the overall risk of bias [23,26]. Thus, in this research, studies with drop-out rates less than 25% were regarded as having a low risk of bias [25,26].…”
Section: Discussionmentioning
confidence: 90%
“…The procedure of sealing involves the application of a resin sealant, polyurethane tape or adhesives after tooth separation [19][20][21][22][23]. Previous systematic reviews and meta-analyses have shown that micro-invasive treatments are more effective than non-invasive treatments [3,11,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…One cannot fail to mention, however, that for the resin infiltration, to our knowledge, just a single commercial product holds the patent so that this fact can restrict its use. When it was not available, professionals can use other approaches, such as fluoride toothpaste and dental floss, and/or fluoride varnish, although these conventional management are less effective, probably because they demand a high level of patient compliance [42]. The use of fluoride toothpaste has been recommended in a few documents [22,23,32], although it is easy to apply and is currently recommended as a prevention measure secondary to ECC.…”
Section: Discussionmentioning
confidence: 99%